Exploration of the fear of missing out internet based on demography - Yuda Syahputra; Miswanto Miswanto; Merri Hafni (International Journal of Evaluation and Research in Education (IJERE), 2023)
Rapid technological developments make it easier for humans to carry out daily activities. Technology that is experiencing very rapid development today is information technology, one of which is a smartphone. Smartphones require internet access to be able to perform as a sophisticated mobile phone. The purpose of this study is to measure the difference in fear of missing out (FoMO) internet students based on gender, faculty, and domicile based on the area of residence. The method in this study uses descriptive comparative, which combines two-way analysis of variance (ANOVA) with Rasch racking model by transforming raw data into logarithmic data. The data in this study were five-point Likert scale polytomy data collected using the FoMO scale instrument which was disseminated online and the research data were analyzed using the Rasch model. The findings show that there are significant differences in FoMO internet in terms of men and women. Furthermore, this study discusses differences in the FoMO internet regarding faculty and domicile, therefore a context is needed to improve the alignment program with technology counseling.